Cross-linking of γ-cyclodextrin using non-toxic polyethylene glycol spacer units - Dossi, Eleftheria; Bolton, Morgan; Kister, Guillaume; Afsar, Ashfaq (Wiley, 2021)
The crystalline cyclic oligosaccharide γ-cyclodextrin (γCD) is a natural, non-toxic and biodegradable precursor that can be used to prepare innovative polymers. We cross-linked γCD with variable quantities of non-toxic polyethylene glycol diglycidyl ether (PEGDGE) in aqueous NaOH to form 3D structures with tunable physicochemical properties. Mixtures with a 5:1 PEGDGE:γCD molar ratio produced a cross-linked material that was soluble in water and organic solvents, underwent glass transition at –23 °C. The properties of this material were further modified by additional curing with PEGDGE or nitration reaction. Curing produced an insoluble polymeric material with excellent swelling abilities (200% in water) and decreased glass transition temperature to –37 °C. The nitrated cross-linked γCD was soluble in common organic solvents and underwent glass transition at +19 °C, achieving thermal stability below 190 °C. These novel γCD polymers are promising materials for applications in the pharmaceutical and food industries and environmental remediation.
Keywords: swelling; glass transition; non-toxic cross-linker; water soluble; cross-linked γ-cyclodextrin